2000
DOI: 10.1021/jp000392w
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Theoretical Determination of the Electronic Structure of Anisole, Thioanisole, and Methoxy- and Methylthiobenzonitriles:  A Contribution to the Study of Organic Conducting Polymers

Abstract: Gas-phase ionization and attachment energy (IE and AE) values of some p-and o-cyano derivatives of anisole and thioanisole (p-NCPhXCH 3 , X ) O, S; and o-NCPhXR, X ) O, R ) CH 3 ; X ) S, R ) H, CH 3 , and C(CH 3 ) 3 ) have been determined experimentally. The assignments of the spectra, based on those of the parent compounds PhXMe, NCPh, and XMe 2 (Me ) CH 3 ), agree with the results of theoretical HF/6-31G** calculations. The calculations correctly reproduce the prevalence of the planar rotamer of the oxy deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 50 publications
4
10
0
Order By: Relevance
“…To discuss the orientation of the thioether group relative to flanking phenyl rings of 1 to 3 , parent thioanisole is taken as a reference for a planar conformation. Although the equilibrium conformation of neutral thioanisole is still under debate due to divergent experimental results, there is no doubt about the planarity of its radical cation because it profits from a delocalization of the unpaired electron into the main phenyl π-system.…”
Section: Resultsmentioning
confidence: 99%
“…To discuss the orientation of the thioether group relative to flanking phenyl rings of 1 to 3 , parent thioanisole is taken as a reference for a planar conformation. Although the equilibrium conformation of neutral thioanisole is still under debate due to divergent experimental results, there is no doubt about the planarity of its radical cation because it profits from a delocalization of the unpaired electron into the main phenyl π-system.…”
Section: Resultsmentioning
confidence: 99%
“…discussed here. 45,46,61,63,83 We only present the results of calculations relevant to the protonated species. Similar to protonated phenol, 84 there are several protonation sites on neutral anisole and p-fluoroanisole corresponding to different positions of carbon atoms on the benzene rings.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the present study, protonation effects on the electronic transition energies and photophysical behavior of anisole and p-fluoroanisole will be addressed based on the CC2/MP2 methods. Anisole has been the subject of many experimental [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and theoretical [61][62][63] studies. The high resolution S 1 -S 0 electronic excitation spectrum of anisole has been recorded in a molecular beam experiment by F. Lahmani et al 64 and later by C. G. Eisenhardt et al 48 It has been shown that the band origin of the S 1 -S 0 electronic transition of anisole lies at 36 386 cm À1 (4.512 eV).…”
Section: Introductionmentioning
confidence: 99%
“…In several neutral molecules, information on the relative weight of the two conformers and the rotational energy barrier (i.e., the energy difference between the planar and the perpendicular conformers) has been determined by PES measurements [1][2][3] as well as by theoretical calculations. 3,4 A different situation appears to hold for the corresponding aromatic sulfide radical cations. ESR experiments indicate that the planar conformation is the predominant one, which means that the conjugation between the sulfur and the aromatic π system in the radical cation is much more important than the steric interactions.…”
Section: Introductionmentioning
confidence: 99%